2006
DOI: 10.1074/jbc.m506667200
|View full text |Cite
|
Sign up to set email alerts
|

Stanniocalcin 1 Acts as a Paracrine Regulator of Growth Plate Chondrogenesis

Abstract: During embryogenesis, the expression of mammalian stanniocalcin (STC1) in the appendicular skeleton suggests its involvement in the regulation of longitudinal bone growth. Such a role is further supported by the presence of dwarfism in mice overexpressing STC1. Yet, the STC 1 inhibitory effect on growth may be related to both postnatal metabolic abnormalities and prenatal defective bone formation. In our study, we used an organ culture system to evaluate the effects of STC on growth plate chondrogenesis, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 50 publications
3
45
2
Order By: Relevance
“…Other studies have demonstrated that TSA could promote apoptosis induced by Dox treatment (Karagiannis et al 2004, Rho et al 2005 via the activation of p53-signaling pathway (Magnelli et al 1995, Brantley-Finley et al 2003, Wang et al 2004. Human STC1 has been suggested to be a putative p53 downstream target and is involved in apoptosis (Wu et al 2006, Lai et al 2007, Law et al 2008, Nguyen et al 2009. In this study, the data of western blotting, real-time PCR, and p53-luciferase reporter assays showed that p53 was activated in the Dox-treated cells.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Other studies have demonstrated that TSA could promote apoptosis induced by Dox treatment (Karagiannis et al 2004, Rho et al 2005 via the activation of p53-signaling pathway (Magnelli et al 1995, Brantley-Finley et al 2003, Wang et al 2004. Human STC1 has been suggested to be a putative p53 downstream target and is involved in apoptosis (Wu et al 2006, Lai et al 2007, Law et al 2008, Nguyen et al 2009. In this study, the data of western blotting, real-time PCR, and p53-luciferase reporter assays showed that p53 was activated in the Dox-treated cells.…”
Section: Discussionsupporting
confidence: 54%
“…Our previous study has demonstrated the epigenetic regulation of STC1 gene expression in apoptotic cancer cells treated with histone deacetylase (HDAC) inhibitors (Law et al 2008). The possible roles of STC1 in apoptosis have been reported by different laboratories (Zhang et al 2000, Wu et al 2006, Lai et al 2007, Block et al 2009, Nguyen et al 2009). The transcriptional relationship between p53 (TP53) and STC1 has also been suggested (Lai et al 2007); however, the underlying regulatory mechanism is not clear.…”
Section: Introductionmentioning
confidence: 94%
“…In light of our findings, it appears that STC1 functions in response to cellular stress to control the cell death vs survival decision, and this is consistent with two recent studies. In the first, recombinant STC1 protein resulted in an increase in the number of apoptotic chondrocytes in the growth plate of cultured rat metatarsals (Wu et al, 2006), and in the other, STC1 expression was found to be regulated by p53, and was correlated with an increase in apoptosis of CNE-2 cells (Lai et al, 2007). On the basis of our findings, it seems likely that STC1 exerts proapoptotic effects in response to cellular stress through its downregulation of MEK and consequent downregulation of ERK1/2 activity.…”
Section: Regulation Of Oxidative Stress Response By Stc1mentioning
confidence: 99%
“…Surprisingly, the primary haemotrophic exchange unit of the non-invasive allantochorionic placenta, the microcotyledon, is not fully established until day 120 of pregnancy [34]. For these reasons, the amounts of endometrial STC1 secretions as well as maintenance of proper STC1 concentrations in the uterine lumen are important for conceptus development during this time period.STC1 is found in fetal bones or skeletal muscles of mice and acts as a paracrine regulator of chondrogenesis in vitro [20,21]. Transgenic mice overexpressing STC1 exhibit a significant reduction in birth weight and reduced body size in the adult [35,36], suggesting that STC1 has a regulatory role in mammalian fetal or postnatal growth.…”
mentioning
confidence: 99%